2019
DOI: 10.3758/s13428-019-01197-2
|View full text |Cite
|
Sign up to set email alerts
|

Development and validation of a high-speed video system for measuring saccadic eye movement

Abstract: Laboratory-based retroreflective and magnetic scleral search-coil technologies are the current standards for collecting saccadometric data, but such equipment is costly and cumbersome. We have validated a novel, portable, high-speed video camera-based system (Exilim EX-FH20, Casio, Tokyo, Japan) for measuring saccade reaction time (RT) and error rate in a well-lit environment. This system would enable measurements of pro-and antisaccades in athletes, which is important because antisaccade metrics provide a val… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 59 publications
0
9
0
Order By: Relevance
“…Based on the sample size used in previous related works (Brooks et al., 2019; Niehorster et al., 2020), 25 healthy adults were initially included in the present study, 7 participants were excluded due to poor behavioral performance (fixation duration of 10% trials below than 300 ms, which follow the calibration procedure of commercialized eye‐trackers; n = 3), problems with eye‐tracking (missing trials >10%; n = 2), and EEG data quality (impedances of 1/3 electrodes >20 kΩ; n = 2). The final sample consisted of 18 participants (11 females) with a mean age of 20.71 years (SD = 1.83).…”
Section: Methodsmentioning
confidence: 99%
“…Based on the sample size used in previous related works (Brooks et al., 2019; Niehorster et al., 2020), 25 healthy adults were initially included in the present study, 7 participants were excluded due to poor behavioral performance (fixation duration of 10% trials below than 300 ms, which follow the calibration procedure of commercialized eye‐trackers; n = 3), problems with eye‐tracking (missing trials >10%; n = 2), and EEG data quality (impedances of 1/3 electrodes >20 kΩ; n = 2). The final sample consisted of 18 participants (11 females) with a mean age of 20.71 years (SD = 1.83).…”
Section: Methodsmentioning
confidence: 99%
“…Fiber optic cables (Simplex 1.0 mm Industrial Fiberoptics, Tempe, AZ), in series with the light board, were secured in the camera field of view to record the timing of the target light on the video system. 36 In the second season, electro-oculography (EOG) was used to capture participants' saccade latency and direction. [38][39][40][41] Participants were fitted with three disposable surface electrodes (AM-N00S/E, AMBU Blue Sensor Adhesive Snap Electrode; Ambu Inc, Glen Burnie, MD) placed at the outer canthi of each eye and the center of the forehead.…”
Section: Saccade Apparatus and Proceduresmentioning
confidence: 99%
“… 93–99 This method correlates with concussion symptoms in children and adults and has promising utility as a rapid, objective, and non-invasive aid for diagnosis. Several oculomotor measures have been investigated for use as potential biomarkers of altered brain function after TBI, including metrics of fixation, smooth pursuit, saccades, 100 and convergence. 101 One study demonstrated that oculomotor assessment may be an indicator of decreased integrity of frontal white matter tracts and of altered attention and working memory functioning.…”
Section: Diagnostic Biomarkersmentioning
confidence: 99%